High Prevalence of Malnutrition in Geriatric Patients With Solid Organ Cancer—An Institutional Study - Ujjawal Kumar Shriwastav; Deepak Sundriyal; Mridul Khanna; Neethu Sunny; Amit Sehrawat; Minakshi Dhar (JCO Global Oncology, 2025)
PURPOSEThe demographic transition toward aging heralds an increase in the number of geriatric patients with cancer in India. Comprehensive geriatric assessment (CGA) is a sine qua non for treatment planning and shared decision making in these patients. We aimed to study the prevalence of malnutrition and the associated risk factors in geriatric patients with solid organ cancer.METHODSIn this observational study, treatment-naïve geriatric patients with cancer underwent CGA. We performed a Mini Nutritional Assessment (MNA) to diagnose malnutrition. Data analysis was done using descriptive statistics, Pearson’s chi-square, Spearman correlation, and multivariable regression analysis to assess the factors associated with malnutrition.RESULTSOne hundred forty-two patients were included in the analysis. The median age was 67 (range, 60-88) years, with a male preponderance of 73.2% (n = 104) and a stage IV disease of 75.4% (n = 107). Most patients, 91.6% (n = 130), had abnormal MNA scores. Nearly one third of the patients, 35.2% (n = 50), were underweight (BMI <18.5 kg/m2). Poor performance status (PS) was seen in 66.2% (n = 94) of the patients. Poor appetite 79.6% (n = 113) was the most common risk factor, followed by addictions (74.6%, n = 106), chronic constipation (35.9%, n = 51), and polypharmacy (21.8%, n = 31). Cognitive impairment and depression were seen in 35.2% (n = 50) and 57.1% (n = 81) of the patients, respectively. The study found a significant correlation of MNA with age (P = .048), depression (P < .001), PS (P < .001), functional decline (P < .001), and cognition (P < .001).CONCLUSIONThere exists a widespread prevalence of malnutrition and amenable risk factors in geriatric patients with cancer. Nutritional assessment is essential, and interventions should be implemented to improve clinical outcomes.